2017
DOI: 10.1002/aic.15841
|View full text |Cite
|
Sign up to set email alerts
|

A novel route for green conversion of cellulose to HMF by cascading enzymatic and chemical reactions

Abstract: In this work, a novel route to deconstruct cellulose into 5‐hydroxymethylfurfural (HMF) by cascading enzymatic and chemical reactions is reported. For biocatalyst preparation, Fe3O4 nanoparticles encapsulated SBA‐15 with appropriate pore size was synthesized and utilized as magnetic scaffolds for the immobilization of cellulase. For chemical catalyst preparation, sulfated zirconium dioxide conformed monolayers were grafted on SBA‐15 template to create thermally robust mesoporous catalysts with tunable solid ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Moreover, as high as 64.25% of HMF yield can be obtained from glucose, further confirming the high catalytic performance of catalyst‐2 with optimal acid‐base strength. The acid and base active sites have been previously reported to work synergistically for cellulose transformation, in which isomerization process of glucose to fructose was promoted by base sites, and the dehydration reaction of reactively formed fructose to HMF was directed by acid sites ,,,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as high as 64.25% of HMF yield can be obtained from glucose, further confirming the high catalytic performance of catalyst‐2 with optimal acid‐base strength. The acid and base active sites have been previously reported to work synergistically for cellulose transformation, in which isomerization process of glucose to fructose was promoted by base sites, and the dehydration reaction of reactively formed fructose to HMF was directed by acid sites ,,,…”
Section: Resultsmentioning
confidence: 99%
“…HMF can derive many downstream products, including 2,5‐dimethylfuran, 2,5‐diformylfuran, 2,5‐furandicarboxylic acid, levulinic acid, 1,6‐hexanediol, adipic acid, caprolactam, and caprolactone, which were applied diffusely to medicine, plastics and optoelectronic, have great potential alternative to burn coal‐based and oil‐based chemical synthetic monomer ,. Therefore, employing the most abundant organic compound of inedible cellulose as feed stock for HMF synthesis has been hot spots in the past decades . Cellulose is formed by glucose unions through β‐1, 4‐glucosidic, which can be transformed into other small molecules, including ethanol, glucose and HMF by the efficient catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…This pretreatment of media converted cellulose to glucose and glucose to HMF, while HMF and glucose yields were 43.6% and 86.2%, respectively (Scheme 1). The results obtained from enzymatic cascades and reaction systems prove that this method can be applied as an operative route for biomass energy maintenance [51]. In another study, Trichoderma reesei cellulase was immobilized on two different nanomatrices (MNPs and silica nanoparticles (SNPs)) to improve enzymatic efficiency.…”
Section: Cellulase Immobilization On Silica-functionalized Mnpsmentioning
confidence: 94%
“…Ionic liquids (ILs) exhibit fascinating range of properties during the course of the last two decades which include high thermal and chemical stability, un‐flammability, suitable solvation behaviors and un‐volatility . Some recent studies have reported that ILs also show outstanding dissolving property for some cellulosic derivatives that insoluble in traditional solvents . Additionally, they are liquid in a wide temperature range and show interesting electrochemical behaviors .…”
Section: Introductionmentioning
confidence: 99%